Combinatory Effects of Resveratrol and Curcumin in a Murine Model of Acuteon Chronic Liver Failure - Zhang, Jing; Wang, Xiaohong; Li, Qingchun; Mou, Wenqian; Zhu, Ting; Ba, Huanhuan; Mirzaee, Hamed; Yang, Shujuan (Indian Journal of Pharmaceutical Education and Research)
Objectives: Acute-on-Chronic Liver Failure (ACLF) in cirrhosis patients involves rapid health decline, organ failure, and high mortality. This study aimed to assess the therapeutic effects of curcumin and resveratrol in treating ACLF in mice. Materials and Methods: ACLF was induced in 6-8-week-old C57BL6 mice (20-24 g) by chronic liver damage and carbon tetrachloride (CCl4) injections for 10 weeks, followed by acute injury via Acetaminophen (APAP) and Lipopolysaccharide (LPS). Mice were divided into four groups and received intraperitoneal injections three times a week for three weeks: 1) control (ACLF); 2) resveratrol (40 mg/kg); 3) curcumin (25 mg/kg); 4) curcumin + resveratrol (15 mg/kg + 26 mg/kg). Blood and tissues were collected for histological, cell death, and cytokine analysis. Results: Hepatoprotective effects were evident as treatments reduced serum levels of ALT, IL-18, TNF-α, IFN-γ, and hepatocyte apoptosis, as shown by TUNEL analysis. IL-10 levels increased in treatment groups. Mechanistically, the treatment reduced pro-apoptotic and pro-inflammatory markers, while enhancing anti-inflammatory and cell-survival pathways. Conclusion: The results suggest that curcumin and resveratrol mitigate liver damage by modulating apoptotic pathways and inflammatory responses in mice with ACLF.
Keywords: Resveratrol; Curcumin; Acute-on-chronic Liver Failure; Combination Therapy.